Sources, spatial distribution and characteristics of marine litter along the west coast of Qatar - S. Veerasingam (9648980) (2020)
The spatial distribution, sources and characteristics of marine litter (ML) from 36 locations spread over 12 beaches along the west coast of Qatar have been assessed. A total of 2376 ML items with varying sizes were found with an average abundance of 1.98 items/m2. The order of abundance of ML along the coast was as follows: plastics (71.4%) > metal (9.3%) > glass (5.1%) > paper (4.4%) > fabric (4.0%) > rubber (3.9%) > processed wood (2.0%). Locations in the south and northwest coasts of Qatar had significantly higher concentrations of ML. Surprisingly, nearly 47% of the beached polyethylene terephthalate (PET) bottles were derived from the countries bordering the Arabian/Persian Gulf (Gulf), and most of them were produced in the last 2 years. The plastic materials were drifted by winds and currents to the Qatar coast. Gulf circulation provides evidence to the pathways of ML beached on the Qatar coast. Other Information Published in: Marine Pollution Bulletin License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.marpolbul.2020.111478